Relativism and Hermeneutical Thinking - Ciancio, Claudio (Religija ir kultūra, 2010)
The traditional concept of truth as adequacy is too limited. It neglects both the reference to the whole and the possibility to think of truth not as the way the world is but as the way it must be. In the latter way truth is entangled with good. The paper seeks to show that this entanglement can be thought of only within an ontology of freedom. First of all it shows that good is the sense of being that is truth in its most radical meaning. Secondly it shows that sticking to truth and acknowledgement and rejection of error require a practice of freedom. In conclusion freedom shows itself as origin of truth and at the same time as condition of its acceptance or rejection.Is it possible in a relativistic society to propose again the question of truth in morality, right and, even before, in metaphysics? The paper wants to answer the question in two steps. First it is showed that moral and philosophical questions cannot be treated by an objectifying thought. Secondly it is showed that, despite of this, a different form of truth and universality is achievable. Objectivity defines only a particular and limited form of truth. As moral, religious and philosophical truth is non-exhaustible, it reveals itself only in interpretations. Every authentic interpretation says the truth without fulfilling it. Interpretation is not arbitrary and does not renounce the control of the reason and its dimension of universality. In this way hermeneutics gives better ground to the claims of tolerance and dialog than the one promoted by relativism. Furthermore it provides better answer to the claims of truth issued by objectivistic metaphysics and ethics.
Keywords: truth; relativism; hermeneutical thinking; ontology of freedom